Double tricrystal nucleation behavior in Pb-free BGA solder joints. (July 2019) - Han, Jing; Guo, Fu
Abstract: The orientations of tin grains in a solder joint have a significant influence on its inhomogeneous deformation behavior under thermomechanical fatigue (TMF). In this paper, the tin orientations in as-solidified BGA joints were observed in detail by electron backscattering diffraction (EBSD). Double twinning of tin in the process of solidification was observed in the Sn-based solder joints. Although the morphologies of these twinned microstructures differed (beachball or intertwined), four orientations of tin grains, with each twin grain sharing a corporate [100] or [010] axis, were observed and analyzed in these systems. The results showed that the difference in orientation between the two groups of double tricrystals was in the range of 80° to 90°. The accurate misorientations were calculated to be 79.1°, 82.9° and 86.5°, corresponding to 57.2° and 62.8°. In a joint comprising 9 grains, there were 3 groups of double tricrystals. A joint comprising two grains, involving 55–65° tricrystal misorientations and a corporate [100] rotation axis, was practically a tricrystal. The joints exhibiting 4–9 grains with misorientations close to 60° (with a [100] or [010] axis) and 85° were composed of 1–3 groups of double tricrystals. Highlights: Double twinning of tin during solidification from the melt was observed. Four orientations with the same twin grain were found in double twinning system. The two groups of double twined orientations is in the range of 80° to 90°. For a joint comprised of 9 grains, there were 3 groups of double tricrystals. Joints presenting 4–9 grains were composed of 1–3 groups of double tricrystals.